2018
DOI: 10.1371/journal.pone.0201951
|View full text |Cite
|
Sign up to set email alerts
|

Multi-year data from satellite- and ground-based sensors show details and scale matter in assessing climate’s effects on wetland surface water, amphibians, and landscape conditions

Abstract: Long-term, interdisciplinary studies of relations between climate and ecological conditions on wetland-upland landscapes have been lacking, especially studies integrated across scales meaningful for adaptive resource management. We collected data in situ at individual wetlands, and via satellite for surrounding 4-km2 landscape blocks, to assess relations between annual weather dynamics, snow duration, phenology, wetland surface-water availability, amphibian presence and calling activity, greenness, and evapotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 103 publications
0
13
0
Order By: Relevance
“…Yet, these data are necessary for resource managers and other stakeholders to understand the nature of real changes, not those simply predicted by risk models [ 21 ], and to manage resources effectively and adaptively in the face of climate change. This lack of critical information motivated us to design and implement a study integrated across scales, sensors, and disciplines to assess recent relations among temperature, precipitation, wetland and upland water availability, and the statuses of amphibian populations in our study areas [ 27 ]. Our analysis of the first five years of data collection provided an opportunity to further evaluate our approach for executing the remote sensing component of the assessment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Yet, these data are necessary for resource managers and other stakeholders to understand the nature of real changes, not those simply predicted by risk models [ 21 ], and to manage resources effectively and adaptively in the face of climate change. This lack of critical information motivated us to design and implement a study integrated across scales, sensors, and disciplines to assess recent relations among temperature, precipitation, wetland and upland water availability, and the statuses of amphibian populations in our study areas [ 27 ]. Our analysis of the first five years of data collection provided an opportunity to further evaluate our approach for executing the remote sensing component of the assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Bottcher et al [ 114 ] found close correspondence between the beginning of photosynthetic activity (from in-situ CO 2 fluxes) and the timing of snowmelt as the ground in coniferous forest began to be exposed. Results by Sadinski et al [ 27 ] suggest it is difficult to ignore snow/snowmelt in studying land-surface phenology, as they found green-up to be closely aligned with the timing of snowmelt in years when snow melted later, but not in years when snow melted earlier. Ultimately, we need an improved method for addressing the influence of snow on our ability to detect the onset of green-up, as a good estimate for SOST is critical not only for studying changes in weather/climate conditions in relation to biological responses at the start of the growing season, but also because SOST is used in calculating additional phenological metrics, such as time-integrated NDVI and the length of the season [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations